Experimental Study of Imbibition Characteristics During the Soaking Stage After Fracturing in Tight Reservoirs - Hailong Zhao; Long Xu; Ziqing Liu; Shanglin Wu; Houjian Gong; Yajun Li; Hai Sun; Mingzhe Dong (Energy Science & Engineering)
ABSTRACT The soaking stage is vital for oil production after fracturing in tight reservoirs. However, the roles and contributions of spontaneous imbibition (SI) and forced displacement imbibition (FDI) during this stage are poorly understood. This study gave an in‐depth insight on the imbibition characteristics during the soaking stage under non‐zero initial water saturation conditions by static soaking and dynamic waterflooding of the core. The results indicate that the fluid absorbed by SI in the core is short‐ranged. After SI, there is still a substantial amount of remain oil (30.7%) that can be displaced by subsequent FDI. SI considerably drives oil recovery in small pores (10–100 nm), whereas FDI is more effective in large pores (500–1000 nm). Controlling the rate of fracturing water flowing into the matrix from the fracture can enhance the combined effect of SI and FDI. For reservoirs with high initial water saturation, enhancing FDI effect during the soaking stage is favorable for oil production.